2004
DOI: 10.1007/s00213-004-1999-z
|View full text |Cite
|
Sign up to set email alerts
|

The astroglial protein S100B and visually evoked event-related potentials before and after antidepressant treatment

Abstract: The neuroregenerative activity of moderately increased S100B levels in major depression might be a factor contributing to a decrease of prolonged ERP parameters in major depression during antidepressant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 32 publications
7
34
2
Order By: Relevance
“…Interestingly, S100B was not different between males and females with minor depression, rather it differed between healthy males and females. This finding is in line with previous studies showing no sex differences in major depression (Arolt et al, 2002;Hetzel et al, 2005), but contradicts another one showing increased S100B in females with major depression (Yang et al, 2008). The differences between our and the former study might be attributed to the differences in the studied samples with regard to disease severity and age.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, S100B was not different between males and females with minor depression, rather it differed between healthy males and females. This finding is in line with previous studies showing no sex differences in major depression (Arolt et al, 2002;Hetzel et al, 2005), but contradicts another one showing increased S100B in females with major depression (Yang et al, 2008). The differences between our and the former study might be attributed to the differences in the studied samples with regard to disease severity and age.…”
Section: Discussionsupporting
confidence: 86%
“…Alterations of peripheral biomarkers of brain structure and function might shed light on the pathological changes in central mechanisms. Brain derived neurotrophic factor (BDNF), S100B and neuron specific enolase (NSE) are among the most studied biomarkers in affective disorders, in particular major depressive disorder (Schroeter et al, 2002;Hetzel et al, 2005;Andreazza et al, 2007;Schroeter and Steiner, 2009;Kalia and Silva, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this old/new effect did not normalize shortly after clinical remission [19] . Recent studies indicate that moderately increased S100B levels in major depression might be a factor contributing to changes in ERP parameters in major depression [20,26] . Dietrich et al [20] demonstrated that remitted depressive patients with increased S100B serum levels showed normal ERPs N2 and P3 amplitudes in contrast to reduced N2 and P3 amplitudes in patients with normal S100B levels.…”
Section: Introductionmentioning
confidence: 99%
“…S100B may induce neurogenesis [43] that is required for behavioral effects of antidepressants [44] . Four treatment studies showed that S100B decreases after successful antidepressant treatment [20,21,45,46] . Patients with increased S100B levels had a better therapeutic response than those with normal S100B levels [46] .…”
Section: Discussionmentioning
confidence: 99%